Pendidikan Islam dalam Perspektif Emha Ainun Nadjib - Fathur Rofi'i; Iskandar Dzulqarnain (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2023)
This research aims to describe Islamic Education from Emha Ainun Nadjib's Perspective. This type of research is qualitative research. The data collection techniques used were interviews, observation and documentation. Meanwhile, data analysis uses qualitative descriptive analysis techniques. The results of the research show that Emha Ainun Nadjib's thoughts on Islamic education emphasize monotheism, morals (Uswatun Khasanah) and spiritual purification, which are packaged through the phrase Thousand Doors with One Room, namely a method of Islamic education that is likened to a big house, in that big house there are thousands of doors and when we enter the house there is only one large room, without a single bedroom. One large room is defined as Islamic science and thousands of doors are interpreted as various Islamic disciplines such as, the first door is the science of fiqh, the second door is the science of monotheism, the third door is the science of history, the fourth door is the science of mathematics, the fifth door is the science of Sufism, the sixth door is interpretation and so on.